Nutritional Status and Food Consumption of School Children “Dayak Hindu Tribe Bumi Segandu Indramayu” - Sintia Wulandari; Cica Yulia; Ai Nurhayati (Universitas Pendidikan Indonesia (UPI), 2021)
The prevalence of underweight school-age children in Indramayu is the highest in West Java since 2017 even though schoolchildren are experiencing a second rapid growth so that a balanced healthy diet is required to obtain nutritional intake and achieve optimal nutritional status. Children with unbalanced food consumption are susceptible to nutritional problems that affect their growth. The purpose of this study was to analyze the nutritional status and food consumption of schoolchildren of the Dayak Hindu Buddhist Bumi Segandu Indramayu Tribe. This research method is descriptive quantitative with this research design is cross-sectional. The sampling technique used was purposive sampling with inclusion criteria aged 7-12 years and having parents belonging to the Losarang Dayak Tribe. Data was collected by means of anthropometric measurements and interviews using a 2x24 hour food recall sheet. This research was conducted in January – July 2020. The results of this study showed that the nutritional status of the 7-10 year old children group was 78% in the normal category and 11% underweight nutritional status and 11% obese nutritional status. The level of consumption of staple foods is in accordance with the recommendations, the consumption of animal side dishes, vegetable side dishes, vegetables, fruit and milk is not in accordance with the recommended balanced nutrition guidelines. The level of calorie adequacy includes a weight deficit, the level of protein adequacy includes a weight deficit and moderate deficit, and fat and carbohydrates including a weight deficit. Adequate levels of vitamin A, vitamin C, calcium and iron including severe deficits and phosphorus in mild and severe deficits. Recommendations to provide assistance to parents of schoolchildren by posyandu cadres and health institutions regarding the selection of food ingredients and the portion given to suit the nutritional adequacy of school children.